Reconfiguration distribution network with multiple distributed generation operation types using simplified artificial bees colony - Jamian, J.J.; Lim, Z.J.; Dahalan, W.M.; Mokhlis, Hazlie; Mustafa, M.W.; Abdullah, M.N. (International Review of Electrical Engineering, 2012)
The power losses in the distribution network are the critical issues that most researchers are trying to solve nowadays. From the passive distribution network in the last decades, the existing of Distributed Generation (DG) in the system will now allow the network to contribute in supplying some of the power to the load. However, selecting the optimal size of DG plays important role to avoid any drawback to the network. The connection of high capacity and excess number of DG units to electrical power system will lead to very high power losses. This factor makes the optimal size of DG become an important issue for the network to have lower power losses value. Furthermore, the use of reconfiguration method in cooperating with the DG units can help the system to have much lower power loss for the distribution system. Since the reconfiguration only required small investment in controlling method, it is very suitable to be used in improving the voltage profile and the power losses after the optimal DG is achievable. Three types of DG modes are used in the study which is constant voltage mode (PV), constant voltage with reactive power mode (PV with VAR constraint) and constant power mode (PQ mode).The Rank Evolutionary Particle Swarm Optimization (REPSO) and a Novel Simplified Artificial Bee Colony (SABC) are used in finding the optimal size of DG and the best configuration of the network respectively. The results show that the use of reconfiguration technique has improved the power losses as well as the voltage profile for the network even after optimal DG sizing has been achieved.